2005
DOI: 10.1089/apc.2005.19.121
|View full text |Cite
|
Sign up to set email alerts
|

STD/AIDS Knowledge, Attitude, Practice, and Characteristics of Market Vendors in Hefei, China

Abstract: Little is known about the information on sexually transmitted disease (STD)/AIDS in the population working in congregating trading markets in China. A cross-sectional study was conducted among three big congregating trading markets in Hefei City. Seven hundred fifty-two market vendors completed a questionnaire, 333 of two markets provided specimen for STD/HIV testing. The majority of market vendors in China are sexually active youths and adults, and have little education. The market vendors had poor knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The current study uses qualitative methods to investigate the connections between social stratification and HIV sexual risk and the role of social networking practices in facilitating such connections among male market vendors in China. These self-employed men represent an understudied subgroup of migrants who may play an important role in China's growing HIV and syphilis epidemics due to their documented high prevalence of sexually transmitted infections (STI) ( 31 ), low HIV/STI knowledge, and low condom use ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current study uses qualitative methods to investigate the connections between social stratification and HIV sexual risk and the role of social networking practices in facilitating such connections among male market vendors in China. These self-employed men represent an understudied subgroup of migrants who may play an important role in China's growing HIV and syphilis epidemics due to their documented high prevalence of sexually transmitted infections (STI) ( 31 ), low HIV/STI knowledge, and low condom use ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…40 A study among women in Hainan island showed 15% had had premarital sex but none had had extramarital sex, 41 and a study among market vendors in Hefei, a large eastern city, showed 28% had had premarital sex. 42 Other studies have shown higher figures. For example, 52% of those questioned in a study in rural Anhui Province had had premarital sex.…”
Section: Sexual Attitudes and Behavioursmentioning
confidence: 88%
“…The key question is if understanding whether the improvement of knowledge can change migrants’ attitudes towards HIV/AIDS can reduce HIV-related high-risk behaviors. Our previous study found that HIV/STI knowledge is related to attitude and practice for market vendors [ 11 ]. Malcolmet et al’ research showed knowledge alone is not sufficient to eliminate stigmatizing attitudes and behaviors [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%